Kölliker–Fuse GABAergic and glutamatergic neurons project to distinct targets. Issue 8 (14th March 2017) - Geerling, Joel C.; Yokota, Shigefumi; Rukhadze, Irma; Roe, Dan; Chamberlin, Nancy L.
Abstract: The Kölliker‐Fuse nucleus (KF) is known primarily for its respiratory function as the "pneumotaxic center" or "pontine respiratory group." Considered part of the parabrachial (PB) complex, KF contains glutamatergic neurons that project to respiratory‐related targets in the medulla and spinal cord (Yokota, Oka, Tsumori, Nakamura, & Yasui, 2007). Here we describe an unexpected population of neurons in the caudal KF and adjacent lateral crescent subnucleus (PBlc), which are γ‐aminobutyric acid (GABA)ergic and have an entirely different pattern of projections than glutamatergic KF neurons. First, immunofluorescence, in situ hybridization, and Cre‐reporter labeling revealed that many of these GABAergic neurons express FoxP2 in both rats and mice. Next, using Cre‐dependent axonal tracing in Vgat‐IRES‐Cre and Vglut2‐IRES‐Cre mice, we identified different projection patterns from GABAergic and glutamatergic neurons in this region. GABAergic neurons in KF and PBlc project heavily and almost exclusively to trigeminal sensory nuclei, with minimal projections to cardiorespiratory nuclei in the brainstem, and none to the spinal cord. In contrast, glutamatergic KF neurons project heavily to the autonomic, respiratory, and motor regions of the medulla and spinal cord previously identified as efferent targets mediating KF cardiorespiratory effects. These findings identify a novel, GABAergic subpopulation of KF/PB neurons with a distinct efferent projection pattern targeting the brainstem trigeminal sensory system. Rather than regulating breathing, we propose that these neurons influence vibrissal sensorimotor function. Abstract : A new population of GABAergic Kölliker‐Fuse (KF) neurons project to trigeminal sensory nuclei. We propose that these neurons, together with glutamatergic KF neurons that project to the lateral VII, play a role in whisking whereas the remaining glutamatergic KF neurons form part of the respiratory system.